2004
DOI: 10.1111/j.1471-4159.2004.02438.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria dysfunction of Alzheimer's disease cybrids enhances Aβ toxicity

Abstract: Alzheimer's disease (AD) brain reveals high rates of oxygen consumption and oxidative stress, altered antioxidant defences, increased oxidized polyunsaturated fatty acids, and elevated transition metal ions. Mitochondrial dysfunction in AD is perhaps relevant to these observations, as such may contribute to neurodegenerative cell death through the formation of reactive oxygen species (ROS) and the release of molecules that initiate programmed cell death pathways. In this study, we analyzed the effects of beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
175
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(181 citation statements)
references
References 41 publications
6
175
0
Order By: Relevance
“…It is also possible that valinomycin could cause a small increase in A␤ import by physically disrupting mitochondrial membranes. Interestingly, A␤ by itself has been reported to cause mitochondrial depolarization (19). Import of matrix proteins (26) and integration of hydrophobic carrier proteins into the inner membrane requires a membrane potential (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that valinomycin could cause a small increase in A␤ import by physically disrupting mitochondrial membranes. Interestingly, A␤ by itself has been reported to cause mitochondrial depolarization (19). Import of matrix proteins (26) and integration of hydrophobic carrier proteins into the inner membrane requires a membrane potential (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mitochondrial A␤ accumulation impairs neuronal function and, thus, contributes to cellular dysfunction in a transgenic APP mouse model (13). It is noteworthy that in AD at an early stage there is already a reduction in the number of mitochondria (14), the brain glucose metabolism is decreased (15), and the activities of both tricarboxylic acid cycle enzymes (16) and cytochrome c oxidase (COX) are reduced (17)(18)(19)(20). In vitro studies with isolated mitochondria suggest that A␤ 1-42 inhibits COX activity in a copper-dependent manner (21).…”
mentioning
confidence: 99%
“…Compromised brain metabolism is an early indicator of AD in both preclinical and clinical investigations [31]. Previous studies have suggested that a decrease in brain bioenergetics may be a useful biomarker to predict disease decades before symptoms [33][34][35][36]. Decreases in mitochondrial bioenergetics, metabolic enzyme expression and activity, cerebral glucose metabolism, along with increased oxidative stress, Aβ deposits within mitochondria, and expression of ABAD are associated with the prodromal state of AD [34,[37][38][39][40][41][42].…”
Section: Current Strategies Targeting Mitochondria and Bioenergetics mentioning
confidence: 99%
“…A decline in mitochondrial function can occur decades prior to clinical diagnosis of AD and thus may serve as a biomarker of AD risk, as well as a therapeutic target [12,24,32,67]. Preclinical in vitro and in vivo AD models have demonstrated a decline in mitochondrial function, including reduced mitochondrial respiration, decreased metabolic enzyme expression and activity, increased oxidative stress, and increased mitochondrial Aβ load and ABAD expression, prior to AD pathology [12,13,15,24,34,38]. A series of mitochondrial enhancer candidates have been proposed and investigated in preclinical and clinical studies for AD prevention and treatment ( Table 2).…”
Section: Mitochondrial Bioenergetics As a Therapeutic Targetmentioning
confidence: 99%
“…In NT2 cells expressing mtDNA from AD subjects (AD cybrids), exposure to Aβ produces excessive mitochondrial membrane potential depolarization, increased cytoplasmic cytochrome c, and elevated caspase-3 activity compared to normal cybrids. Thus the induction of multiple constituents of the mitochondrial apoptosis pathway by Aβ is dependent on the mitochondria carried by the cell [25]. Finally, there has been an examination of the distribution of mtDNA haplogroups in AD cases and controls with one study reporting a protective effect for APOE e4 carriers with the K or U haplogroup, while another reported no relationship to APOE status but rather differential risk according to haplogroup and sex [9;10].…”
mentioning
confidence: 99%